Chairing Transition: Leading a Department Through a Merger - David M Keller (Academic Chairpersons Conference Proceedings, 2015)
This session will focus discussion on the impact of merging pre-existing departments and/or colleges to form a new entity on Chair leadership strategies. Participants will discuss factors to be considered to ensure successful transition for the department and maximize growth in the new entity.
Keywords: integration; leadership; new college; resource management; merging departments